2015
DOI: 10.1007/s12178-015-9303-x
|View full text |Cite
|
Sign up to set email alerts
|

Knee cartilage defect: marrow stimulating techniques

Abstract: Painful chondral defects of the knee are very difficult problems. The incidence of these lesions in the general population is not known since there is likely a high rate of asymptomatic lesions. The rate of lesions found during arthroscopic exam is highly variable, with reports ranging from 11 to 72 % Aroen ( Examples of current attempts at cartilage restoration include marrow stimulating techniques, ostochondral autografts, osteochondral allografts, and autologous chondrocyte transplantation. Current research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…However, these techniques are only focused on the repair/regeneration of the cartilage, while defects greater than 6-8 mm in depth (OC defects) require the addition of a bone graft [18]. Instead, relatively small OC defects, <2 cm 2 , can be treated using microfracture surgery where holes are created in the subchondral bone to access the bone marrow and release stem cells and growth factors (Figure 2A) [17,[67][68][69][70]. While this method can produce new cartilage, histological analysis shows this to be mostly composed of fibrocartilage [70] which lacks the lubricative and load distribution properties typical of the native articular hyaline cartilage [54].…”
Section: Existing Surgical Treatments For Osteochondral Defectsmentioning
confidence: 99%
“…However, these techniques are only focused on the repair/regeneration of the cartilage, while defects greater than 6-8 mm in depth (OC defects) require the addition of a bone graft [18]. Instead, relatively small OC defects, <2 cm 2 , can be treated using microfracture surgery where holes are created in the subchondral bone to access the bone marrow and release stem cells and growth factors (Figure 2A) [17,[67][68][69][70]. While this method can produce new cartilage, histological analysis shows this to be mostly composed of fibrocartilage [70] which lacks the lubricative and load distribution properties typical of the native articular hyaline cartilage [54].…”
Section: Existing Surgical Treatments For Osteochondral Defectsmentioning
confidence: 99%
“…The cartilage tissue formed can fill the defect partially or completely. When the healing tissue was analyzed at 8 weeks, it was observed that it consisted of fibrous tissue (29%), fibro cartilaginous tissue (30%), granulation tissue (12%), bone tissue filling the defect (10%) and hyaline-like cartilage tissue (12%) (1) . The quality of the repaired tissue was still a matter of discussion.…”
Section: Graphmentioning
confidence: 99%
“…On the basis of experimental and clinical studies, the use of continuous passive motion (CPM) of the knee together with a period of non-weight bearing had been widely adopted for the management of chondral defects, especially after microfracture. Salter et al (30) stated that perhaps the most influential investigators to advocate the use of CPM in conjunction with biologic resurfacing procedures, were believing that the quality of chondral repair tissue was markedly improved by the "dynamic compression" that modulated the regenerative potential of chondrocytes (1) .…”
Section: Does Lesion Size Influence Outcome With Microfracture ?mentioning
confidence: 99%
See 1 more Smart Citation
“…8 , 9 More recently, a microdrill (PowerPick; Arthrex, Naples, FL) has been introduced as a technical alternative to more traditional awl and hammer techniques. 10 , 11 Histologic examinations of bone after treatment with a microdrill demonstrate decreased bony compaction and preservation of “bony channels” to marrow stroma relative to a traditional mallet and awl. 12 However, the impact of technique variations on outcomes has yet to be determined, 13 , 14 , 15 although based on histologic changes, improved outcomes may be expected.…”
mentioning
confidence: 99%